2,2′-Diazinodimethylidyne)di-o-phenylene) dibenzoate - Chattopadhyay, Basab (International Union of Crystallography, 2008)
The title compound, C(28)H(20)N(2)O(4), was synthesized by the reaction of 2-(hydrazonomethyl)phenyl benzoate with iodine. The molecule possesses a crystallographically imposed center of symmetry at the mid-point of the hydrazine N—N bond. The substituents at the ends of the C=N bonds adopt an E,E configuration. Intermolecular C—H⋯π(arene) hydrogen bonds and aromatic π–π stacking interactions [centroid–centroid distance 3.900 (1) Å] link the molecules into (100) sheets. In addition, there is an intermolecular C—H⋯O hydrogen-bond interaction.